The Principles of Clinical Cytogenetics - Gersen, Steven L.; Keagle, Martha B.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
In this thoroughly revised and expanded third edition of the highly praised classic, The Principles of Clinical Cytogenetics, a panel of hands-on experts update their descriptions of the basic concepts and interpretations involved in chromosome analysis to include the many advances that have occurred in the field. Among the highlights are a full chapter devoted to advances in chromosome microarray, soon to become a standard of care in this field, as well as an update on chromosome nomenclature as reflected in ISCN 2009. Other features include an update on automation to reflect the current state of the art, an update on hematopoietic neoplasms to reflect the new WHO guidelines, and updates on all regulatory changes that have been implemented. Cutting edge and readily accessible, The Principles of Clinical Cytogenetics, Third Edition offers physicians who depend on the cytogenetics laboratory for the diagnosis of their patients, students in cytogenetics programs, graduate and medical students studying for board examinations, cytogenetics technologists, and cytogeneticists a clear understanding of what happens in the cytogenetics laboratory to facilitate accurate and timely diagnoses.
History of Clinical Cytogenetics -- DNA, Chromosomes, and Cell Division -- Human Chromosome Nomenclature: An Overview and Definition of Terms -- Basic Cytogenetics Laboratory Procedures -- The Essentials of Light Microscopy -- Quality Control & Quality Assurance -- Instrumentation in the Cytogenetics Laboratory -- Autosomal Aneuploidy -- Structural Chromosome Rearrangements -- Sex Chromosomes, Sex Chromosome Disorders, and Disorders of Sex Development -- The Cytogenetics of Infertility -- Prenatal Cytogenetics -- The Cytogenetics of Spontaneous Abortion -- Chromosome Instability -- The Cytogenetics of Hematologic Neoplasms -- The Cytogenetics of Solid Tumors -- Fluorescence in situ Hybridization (FISH) -- Microarray-Based Cytogenetics -- Fragile X: A Family of Disorders: Changing Phenotype and Molecular Genetics -- Genomic Imprinting and Uniparental Disomy -- Genetic Counseling.
Keywords: Medicine; Human genetics; Hematology; Oncology; Pathology; Biomedicine; Cytogenetics; Human Genetics; Pathology; Hematology; Oncology